Mobile-Based Design of Information System for Vocational Internship Activities for Vocational Students - Alya, Rizwana; Ikhwan, Ali (Politeknik Ganesha Medan, 2022)
Information technology that is growing slowly in modernization follows the development of an increasingly aging population, and has an impact on group and individual life. Information technology also provides easy and big things related to collecting the right information directly or indirectly, and citizens get various benefits that are taken through their technological innovations, covering all aspects of life and education. An obstacle that is felt by Brigjend Katamso II Medan Vocational School is still done manually when managing student Internship activities, for example, collecting information on internship student classes, attendance, data on internship places and groups, supervision and student activities and submitting grades are also still manual. Therefore, it is necessary to design an information system for student Internship activities using API pages and the Java programming language so that admins, supervisors, field supervisors and students of SMK Brigjend Katamso II Medan can access this system with their mobile device. In order to implement the application that the researcher wants to create, it will use an R&D approach, so that the data collection methods used are interviewing, observing and studying literature. The development of the system used in this INTERNSHIP activity system is using the RAD method during system development, in order to create a system that provides objective information and can provide assistance to SMK Brigjend Katamso II Medan.